2023
DOI: 10.1038/s41467-023-36230-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for clearing of ribosome collisions by the RQT complex

Abstract: Translation of aberrant messenger RNAs can cause stalling of ribosomes resulting in ribosomal collisions. Collided ribosomes are specifically recognized to initiate stress responses and quality control pathways. Ribosome-associated quality control facilitates the degradation of incomplete translation products and requires dissociation of the stalled ribosomes. A central event is therefore the splitting of collided ribosomes by the ribosome quality control trigger complex, RQT, by an unknown mechanism. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 69 publications
(90 reference statements)
1
47
0
Order By: Relevance
“…Recent cryoEM structures of yeast RQT–ribosome complexes revealed that prior to ribosome splitting the yeast ASCC3 ortholog, Slh1p, can adopt a more open conformation with fewer direct interactions between the two helicase cassettes as observed in our human ASCC3–TRIP4 complex structure 25 . While in the imaged conformations both Slh1p helicase cassettes are potentially accessible to an RNA substrate, no corresponding substrate density was observed at either Slh1p cassette 25 .…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Recent cryoEM structures of yeast RQT–ribosome complexes revealed that prior to ribosome splitting the yeast ASCC3 ortholog, Slh1p, can adopt a more open conformation with fewer direct interactions between the two helicase cassettes as observed in our human ASCC3–TRIP4 complex structure 25 . While in the imaged conformations both Slh1p helicase cassettes are potentially accessible to an RNA substrate, no corresponding substrate density was observed at either Slh1p cassette 25 .…”
Section: Discussionmentioning
confidence: 50%
“…Recent cryoEM structures of yeast RQT–ribosome complexes revealed that prior to ribosome splitting the yeast ASCC3 ortholog, Slh1p, can adopt a more open conformation with fewer direct interactions between the two helicase cassettes as observed in our human ASCC3–TRIP4 complex structure 25 . While in the imaged conformations both Slh1p helicase cassettes are potentially accessible to an RNA substrate, no corresponding substrate density was observed at either Slh1p cassette 25 . In the observed conformations, mRNA could apparently be accommodated directly at the Slh1p CC, but an Slh1p variant harboring an ATPase-deficient NC (Slh1p K361R ) was required to capture RQT–ribosome complexes at a stage preceding ribosome splitting 25 , indicating that the NC ATPase/helicase activity is also required for the splitting reaction.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations